The Psychology of Habit Formation and Christian Moral Wisdom on Virtue Formation - Pawl, Timothy J. (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2023)
In this paper, I provide an overview of the Christian moral wisdom with respect to virtue formation and character cultivation. I focus in particular on some warnings issued by the great teachers on these topics with respect to the motivations one ought to have in the Christian life. I then discuss some findings of contemporary psychology on habit formation which seem to be at odds with the warnings in Christian moral wisdom. I argue that while there is surface discord between the contemporary psychology of habit formation and Christian moral wisdom, there is in fact a deep concord between them.